2011
DOI: 10.1002/ange.201105536
|View full text |Cite
|
Sign up to set email alerts
|

Structural Study‐Guided Development of Versatile Phase‐Transfer Catalysts for Asymmetric Conjugate Additions of Cyanide

Abstract: Significant advances have been made in the development of catalytic 1,2-asymmetric cyanations using both chiral metal and organic catalysts. [1] In contrast, only a few highly enantioselective catalytic conjugate additions of cyanide ions have been realized despite the potential of such transformations in providing efficient enantioselective access to synthetically valuable chiral building blocks. [2] The first breakthroughs were reported by Jacobsen and co-workers, who described chiral Al-Salen [3] and bimeta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
18
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…[11] Therefore, we focused on the cupreidine-based phase-transfer catalyst, since they have a different mode of hydrogen bonding to substrates. [12] Gratifyingly, an improved ee value of 57 % was observed in the presence of 4 c (entry 3). When the reaction was carried out using the methylether cupreidinium salt 4 d, the desired 5 a was obtained in 49 % with 85 % ee (entry 4).…”
mentioning
confidence: 91%
See 2 more Smart Citations
“…[11] Therefore, we focused on the cupreidine-based phase-transfer catalyst, since they have a different mode of hydrogen bonding to substrates. [12] Gratifyingly, an improved ee value of 57 % was observed in the presence of 4 c (entry 3). When the reaction was carried out using the methylether cupreidinium salt 4 d, the desired 5 a was obtained in 49 % with 85 % ee (entry 4).…”
mentioning
confidence: 91%
“…Rb 2 CO 3 , Cs 2 CO 3 , and K 3 PO 4 showed higher reactivities, but enantioselectivities were lower than those obtained with K 2 CO 3 (entries [8][9][10][11]. A subsequent solvent survey (entries [12][13][14][15][16][17][18][19][20] revealed that benzene was the solvent of choice with regard to enantioselectivity (entry 15). Further improvement of selectivity was observed in the presence of 4 M.S.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, the reported synthetic strategies for the synthesiso fd ihydropyridazinones are normally limited to the condensation of costly substrate goxo acids andh ydrazine. [3] Therefore,t he development of an ew strategyt hat allowsr apid access to dihydropyridazinones from readily accessible starting materials using ap ractical method is still highly desirable and an enduring goal of organic chemistry.…”
mentioning
confidence: 99%
“…The reaction proceeded at 10 8C and resulted in a higher enantioselectivity without an obvious sacrifice of reaction rate (Table 1, entries 1-4). Further screening of the solvents revealed that CH 2 Cl 2 appeared to be the most suitable reaction media (entries [5][6][7][8]. When the catalyst load-ing decreased to 10 mol % or no molecular sieves were added, low selectivity and yield were observed (entries 9-10).…”
mentioning
confidence: 99%